Pengelolaan Sumberdaya Arkeologi Situs Kotacina - Stanov Purnawibowo (Berkala Arkeologi Sangkhakala, 2008)
AbstractCultural Resources Management in Kotacina site must be build to recovery and defend it from lost. Three stakeholders were found in their management of site. They must cooporate their works and duties for built fine Cultural Resources Management.